Identification of Urinary CD44 and Prosaposin as Specific Biomarkers of Urinary Tract Infections in Children With Neurogenic Bladders. Issue 14 (March 2019) - Forster, Catherine S; Haffey, Wendy D; Bennett, Michael; Greis, Kenneth D; Devarajan, Prasad
Purpose: Distinguishing urinary tract infection (UTI) from urinary tract colonization (UTC) in children with neurogenic bladders who require clean intermittent catheterization (CIC) is challenging. Our objective was to identify urinary proteins to distinguish UTI from UTC in CIC-dependent children that have potential to serve as objective markers of UTI. Experimental design: A total of 10 CIC-dependent children were included in the mass spectrometry analysis (UTI = 5, UTC = 5). Quantitative profiling of urine proteins with isobaric protein labeling was performed using tandem mass spectrometry. Candidate markers were normalized using a collective mixture of proteins from all samples. Relative quantitative abundance of proteins across all samples were compared. Proteins with >50% change in the average abundance were identified as proteins of interest, which were then measured using enzyme-linked immunosorbent assay (ELISA) in an additional 40 samples (no growth = 10, UTC = 15, UTI = 15). Results: Mass spectrometry revealed 8 differentially expressed proteins. Of these, apolipoprotein D, alpha-amylase 2B, non-secretory ribonuclease, CD44 antigen, and prosaposin were measurable by ELISA. Concentrations of both CD44 and prosaposin were significantly higher in UTI, with area under the curves (AUCs) of 0.72 and 0.78, respectively. Conclusion: Urinary CD44 and prosaposin are candidate markers that may assist with the diagnosis of UTI in CIC-dependent children.